Investment Advice for Professional Men (Book). - Cannon, Arthur M.; Trefftzs, Kenneth L. (The Accounting Review, 1952)
Reviews the book "Investment Advice for Professional Men," by Howard A. Bolton and Wilford J. Eiteman.